The magnitude of organizational justice affects teachers’ OCB and task performance - Irvandi Gustari; Widodo Widodo (Jurnal Konseling dan Pendidikan, 2022)
This study investigates the effect of organizational justice on teachers' task performance mediated by organizational citizenship behavior (OCB). Research data were collected from 220 teachers of Senior High Schools in Indonesia through questionnaires. The data obtained were analyzed by path analysis supported by descriptive and correlational statistics. The results show that organizational justice significantly affects teachers' task performance, directly or indirectly, mediated by OCB. Thus, teachers' task performance can be improved through organizational justice and OCB. Furthermore, these findings can be discussed as a reference among researchers and practitioners to develop new, better, and comprehensive models of teachers' task performance in the future. This study investigates the effect of organizational justice on teachers' task performance mediated by organizational citizenship behavior (OCB). Research data were collected from 220 teachers of Senior High Schools in Indonesia through questionnaires. The data obtained were analyzed by path analysis supported by descriptive and correlational statistics. The results show that organizational justice significantly affects teachers' task performance, directly or indirectly, mediated by OCB. Thus, teachers' task performance can be improved through organizational justice and OCB. Furthermore, these findings can be discussed as a reference among researchers and practitioners to develop new, better, and comprehensive models of teachers' task performance in the future.